Space Debris: il problema dei rifiuti spaziali - Dussi, Michele (GEOmedia, 2008)
Space Debris: the space garbage problem The dramatic growth in space activities since 1957 has generated a large amount of "in-orbit garbage”, namely space-debris. Many of these are potentially dangerous for space vehicles and/or for the people on Earth. In an acceptable space security framework, a major role is reserved to cooperative space debris monitoring in order to prevent and to mitigate the effects of the problem.